Bilateral symmetry in single leg landings - Bentley, B.; Milburn, P.; Milosavljevic, S.; Carman, A. (ISB Congress, 2006)
The aim of this project was identify differences in kinematics of the knee joint of the dominant and non-dominant legs during a single leg landing task.